Development Mathematics Test Based on Education for Sustainble Development to Measure Middle School Students' Creative Thinking Skills - Widiati, Indah; Herlina, Sari; Zahara, Ely (Proceeding International Conference on Mathematics and Learning Research, 2023)
The design of ESD-based math problems to measure creative thinking skills namely contains indicators of creative thinking skills and is applied in everyday life day. The research design used is formative evaluation (self-evaluation, expert reviews, one-to-one, small group, and field tests). The research results show that from the initial design of the questions (47 students), only 28 questions were valid. After conducting large-scale tests shows that only some students can complete it. It is supported by the results of the written interview which said that the question was a moderate level of difficulty. But there are also those who say that the problem is too easy. With the research results is expected to produce guidelines in designing math-based test questions ESD for students.